Prevalence and factors associated with frequent review of nutrition labeling by adults in Peru - Gómez-Guizado, Guillermo (2023)
Introduction. The absence or little review of nutritional labeling is very frequent, and these provide information on the quality of the food that is going to be acquired and consumed. Objective. To determine the prevalence of the frequent review of nutritional labeling (REN) and its associated factors. Methods. Analytical cross-sectional study that evaluates the data from the Nutritional Food Surveillance by Life Stages (VIANEV) from 2017-2018. REN was considered frequent when the adult always or almost always read the table of nutrients of the products they purchase and/or consume. Estimates and bivariate analyzes were made, associated factors were determined using a generalized linear model of the Poisson family with log link under multiple imputation. Results. It was found that 62,4% do not review the nutritional content labeling. Only 14,9% of adults do so frequently. For the crude model, higher education was associated with a higher prevalence of REN (PR=10,79; 95%CI: 1,49-78,16); and a lower prevalence in rural areas (PR=0,47; 95%CI: 0,31-0,73) and having at least one Unsatisfied Basic Need (PR=0,56; 95%CI: 0,33-0,98). In the adjusted model, an association was found for divorcees (PR=4,24; 95%CI: 1,91-9,41), cohabiting (PR=1,61; 95%CI: 1,04-2,47) and those who consumed 5 or more servings of fruit or vegetables per day (PR=1,77; 95%CI: 1,28-2,44). Conclusions. The review of nutritional labels is not a usual behavior in adults, and its performance was associated with divorced people, cohabitants and with those who consume 5 or more servings of fruits and vegetables.